Pengaruh Personal Branding Raisa Andriana Terhadap Keputusan Pembelian Produk Raine Beauty: Survei Pada Followers Instagram @Officialrainebeauty - Annisa Az-Zahra Rahmawati; Aminah Swarnawati (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2024)
For a public figure, personal branding needs to be considered to build credibility and have self-value, one of which is Raisa Andriana who started her career as a singer to enter the business in the cosmetics industry. The personal branding he does can be an attraction to indirectly market Raine Beauty products. Based on the said, the purpose of this research is to find out Raisa Andriana's personal branding, the purchase decision on Instagram followers @officialrainebeauty and the influence of personal branding "Raisa Andriana" on the decision to buy Instagram followers @officialrainebeauty. The theory used is Personal Branding which includes the Roles, Standards, Style and Purchase Decision dimensions which include the Problem Recognition, Information Search, Evaluation of Alternatives, Purchase Decision, Post Purchase Behaviour dimensions. This research approach is quantitative with the explanatory survey method. Data collection technique with the distribution of questionnaires to 134 respondents Instagram followers @officialrainebeauty. This research uses probability sampling techniques for sampling with the random sampling method. Overall, the results of this study show that the influence of Raisa Andriana's Personal Branding on the product Purchase Decision, respondents responded in agreement (good) in the research questionnaire from all Y variable statements and the magnitude of the influence of Personal Branding Raisa Andriana has a strong and positive relationship with the product Purchase Decision of 0.779 with the percentage of Personal Branding Raisa Andriana affecting the Purchase Decision of Raine Beauty products by 60.7% while the remaining 39.3% are influenced by other factors.